PERSEPSI ORANG TUA TERHADAP PERAN GURU TAMAN PENDIDIKAN AL-QUR’AN (TPQ) DALAM MEMBERIKAN PENDIDIKAN AKHLAK PADA ANAK DI TPQ TAJUL WAQOR KOTA BENGKULU - Rosinta, Sherly; Zulkarnain; Taufiqurrahman, Muhammad (Yayasan Darussalam Bengkulu, 2020)
The purpose of this research is to find out the positive or negative perceptions of parents on the role of TPQ teachers in providing moral education to children at TPQ Tajul Waqor Bengkulu City and find out what are the roles of TPQ teachers in providing moral education to children. The type of research used is qualitative research with a descriptive approach where the research sources consist of parents and TPQ teachers. Data collection techniques using observation techniques, interviews and documentation. Data analysis is carried out by reviewing existing data, then conducting data reduction, presenting data, and drawing conclusions. The results showed that most parents had a good perception of the existence of this TPQ and a bad perception of the role of the TPQ teacher in providing moral education to children. This is evidenced by the results of interviews obtained about the role of TPQ teachers that have not been fully implemented so that children are not optimal in participating in TPQ activities due to the shortage of educators in this TPQ. As for the role of TPQ teachers in providing moral education to children, namely: morals to God such as teaching children to pray and other worship in carrying out Allah's commands, morals to the Prophet such as following the sunnahs of the Prophet Muhammad, morals towards teachers such as respect and obedience to teachers, Morals towards parents are respect and obedience to parents, morals towards fellow friends such as loving each other, and morals towards the environment such as not littering. The supporting factors in this case are iTPQ iTajul iWaqor i, namely adequate facilities and infrastructure, support from the in-laws of these people, the available teaching and learning environment, the competent teacher-in-laws, the large number of Islamic students who have many learning environments. And the inhibiting factor is the lack of educators, so that the learning process does not run optimally according to the expectations of the parents-in-law, so that perceptions arise from parents. For a bad perception of the role of TPQ teachers in providing moral education to children, it will be a correction material for the institution and also its educators.